Geo-Epidemiological Study of Leptospira spp. Infection in Cattle, Feral Cats and Rodents of the Fernando de Noronha Island, Brazil - Ferrer de Morais, Eduardo Guelfer; Magalhães, Fernando Jorge Rodrigues; de Lima Filho, Carlos Diógenes Ferreira; Brandespim, Daniel Friguglietti; de Oliveira, Pollyane Raysa Fernandes; da Costa, Diego Figueiredo; de Azevedo, Sérgio Santos; Mota, Rinaldo Aparecido (Acta Scientiae Veterinariae, 2018)
Background: Leptospirosis is a re-emergent contagious infectious disease, caused by pathogenic leptospires that are transmitted by the urine of infected animals or bacteria-contaminated water and mud. In tropical and subtropical countries it presents high prevalence due to the temperature and humidity conditions that favor the maintenance of the agent in the environment. This disease can affect several species, in Brazilian cattle is an endemic disease, and studies have shown a high occurrence of Leptospira spp. infection in beef and dairy herds. Domestic cats as well as other species of the Family Felidae seem to be resistant to leptospirosis. However, it has been demonstrated under experimental conditions that cats may become infected by ingestion of infected rodents and contaminated water. The present study investigated the occurrence of Leptospira spp. infection in cattle, feral cats and rodents of the Fernando de Noronha Island. Materials, Methods & Results: Fernando de Noronha Island is located 360 km far from Recife and Natal, capitals of the states of Pernambuco and Rio Grande do Norte, Brazil, respectively. It has an area of approximately 18.4 km2 and constitutes the submerged part of a volcanic edifice currently inactive, which base rests 4,000 m deep in the Atlantic Ocean. Blood samples were collected from all the cattle raised in the Island (n = 88), 200 feral cats and 150 rodents, and the sera were screened by MAT (Serogroups: Australis; Autumnalis; Ballum; Bataviae; Canicola; Cynopteri; Djasiman; Grippotyphosa; Hebdomadis; Icterohaemorrhagiae; Icterohaemorrhagiae; Panama; Pomona; Pyrogenes; Sejroe e Tarassovi) for detection of anti-Leptospira spp. antibodies. Initially all sera were screened at 1:100 dilution and those with 50% or more agglutination were titrated at two-fold geometric dilutions. The serum titer was defined as the reciprocal of the highest positive dilution. The plane coordinates obtained by Global Position System (GPS) were used for developing a spatial map of the Fernando de Noronha Island. The geo-referenced data were plotted in the ArcGIS 10.1 software. Approximately 22% (20/88) and 12% (19/150) of the cattle and rodents were serologically reactive against Leptospira spp. antigens, respectively. The antibody titers of cattle ranged from 100 to 800 as shown. All the rodents screened were reactive against only one serovar and their antibody titers ranged from 100 to 3200. None of the serum samples from cats was reactive against the serovars tested. The serogroup Icterohaemorrhagiae predominated among the seropositive cattle, being found in 100% of the reactive samples. In rodents, the serogroups Icterohaemorrhagiae, Djasiman and Australis were responsible for 73.7% (14/19), 21.0% (4/19) and 5.2% (1/19) of the infections, respectively. Discussion: We believe that rodents and cattle play an important role in the dissemination of this disease, thus, it is necessary adopting prophylactic measures aimed at leptospirosis in the study area, in view of the human cases of leptospirosis reported and confirmed in the Island. These results are unprecedented in an insular environment in Brazil. Strategies aimed at better sanitary management of the cattle herds as well as population control of rodents must be implemented in the Fernando de Noronha Island to secure a more sustainable animal production and minimize the risks to public health.